THE MARINE 187OS/188OS RECORD OF THE EOCENE-OLIGOCENE TRANSITION: THE INTERPLAY OF WEATHERING AND GLACIATION - Ravizza G.; Peucker-Ehrenbrink B. (My University, 2003)
Osmium (Os) isotope analyses of bulk sediments from the South Atlantic, Equatorial Pacific, and the Italian Apennines yield a well-dated and coherent pattern of 187Os/188Os variation from the late Eocene to the early Oligocene. The resulting composite record demonstrates the global character of two prominent features of the low-resolution LL44-GPC3 Os isotope record [Pegram and Turekian, Geochim. Cosmochim. Acta 63 (1999) 4053–4058]. These are: (1) a pronounced minimum in 187Os/188Os (0.22–0.27) in the late Eocene, between 34 and 34.5 Ma, and (2) a subsequent rapid increase in 187Os/188Os, to approximately 0.6 by 32 Ma. An ultramafic weathering event and an increased influx of extraterrestrial particles to the Earth are discussed as alternative explanations for the late Eocene 187Os/188Os minimum. Comparison of the 187Os/188Os to benthic foraminiferal oxygen isotope records demonstrates that the nearly three-fold increase in 187Os/188Os from the late Eocene minimum coincides with the growth and decay of the first large ice sheet of the Oligocene (Oi1 [Miller et al., J. Geophys. Res. 96 (1991) 6829–6848]). The fine structure of the Os isotope record indicates that enhanced release of radiogenic Os, unrelated to the recovery from late Eocene minimum, lagged the initiation of the Oi1 event by roughly 0.5 Myr. This record, in conjunction with weathering studies in modern glacial soils [Blum, in: W.F. Ruddiman (Ed.), Tectonic Uplift and Climate Change, Plenum Press, New York, 1997, pp. 259–288; Peucker-Ehrenbrink and Blum, Geochim. Cosmochim. Acta 62 (1998) 3193–3203], suggests that exposure of freshly eroded material during deglaciation following Oi1 enhanced chemical weathering rates, and may have contributed to ice sheet stabilization by drawing down atmospheric carbon dioxide. The improved temporal resolution and age control of the refined Eocene–Oligocene Os isotope record also makes it possible to illustrate the late Eocene Os isotope excursion as a tool for global correlation of marine sediments.
Keywords: Oligocene; Eocene; Cenozoic::Paleogene::Oligocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Олигоцен; Кайнозой::Палеоген::Эоцен